2020
DOI: 10.29105/respyn19.3-3
|View full text |Cite
|
Sign up to set email alerts
|

Relación del índice cintura-talla (ICT) con cintura e Índice de Cintura Cadera como predictor para obesidad y riesgo metabólico en adolescentes de secundaria

Abstract: Introducción: El sobrepeso y obesidad en adolescentes son un problema nutricional, el aumento en la prevalencia combinada es preocupante por los efectos adversos del exceso del peso en salud. El Índice cintura Talla (ICT) ≥0.5 es aceptado como un punto de corte universal y puede ser utilizado para predecir obesidad abdominal/riesgo cardiovascular. Objetivo: Identificar el riesgo de obesidad/riesgo metabólico mediante ICT comparando las medidas antropométricas circunferencia cintura (CC.) e Índice de Cintura C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…Conversely, Castiñeiras et al [9] found a 23% obesity prevalence in adolescents based on WC, while our study reported 29.72%. Regarding WHtR, the survey by Zermeño-Ugarte P et al [12] conducted in Mexico found 32.7% of adolescents obese by WHtR, a figure exceeding that in our study. This rise in adolescent obesity could be linked to consuming inexpensive, high-calorie foods [8] and reduced physical activity, replaced by sedentary lifestyles, including extensive use of technological devices [13].…”
Section: Prevalence Of Obesity Based On Anthropometric Measurementscontrasting
confidence: 98%
See 1 more Smart Citation
“…Conversely, Castiñeiras et al [9] found a 23% obesity prevalence in adolescents based on WC, while our study reported 29.72%. Regarding WHtR, the survey by Zermeño-Ugarte P et al [12] conducted in Mexico found 32.7% of adolescents obese by WHtR, a figure exceeding that in our study. This rise in adolescent obesity could be linked to consuming inexpensive, high-calorie foods [8] and reduced physical activity, replaced by sedentary lifestyles, including extensive use of technological devices [13].…”
Section: Prevalence Of Obesity Based On Anthropometric Measurementscontrasting
confidence: 98%
“…The most alarming chronic disease of the 21st century, obesity, is characterized by what constitutes an abnormal and excessive accumulation of body fat that differs in its definitions and cutoff points depending on age and demographic group alike [1]. While the rising occurrence of this condition in teenagers proves troubling, equal cause for concern stems from its potential long-lasting consequences, especially since not only is its frequency growing, but the implications for their future remain unclear [1][2][3]. Many adolescents dealing with obesity faces ongoing challenges shedding excess weight into their adult years, markedly amplifying the likelihood of severe illnesses such as type 2 diabetes and cardiovascular conditions developing [4].…”
Section: Introductionmentioning
confidence: 99%
“…Variables analyzed: Cardiovascular risk: For this, central obesity was analyzed, using the waist-to-height ratio, which allows categorizing participants into normal adiposity, moderate adiposity, and excessive adiposity [ 6 , 39 , 40 , 41 , 42 ]. Cardiorespiratory capacity: The 20 m shuttle run test was used, measuring the time (s), the speed (m/s), and the number of shuttles completed, according to the protocol and reference values of the Alpha Fitness battery for the school population [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cardiovascular risk: For this, central obesity was analyzed, using the waist-to-height ratio, which allows categorizing participants into normal adiposity, moderate adiposity, and excessive adiposity [ 6 , 39 , 40 , 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%